A New Era of Growth: Reforms to Revitalize the Indian Economy - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
India is currently going through the most significant economic slowdown it has experienced in at least the past 20 years. Prior economic slowdowns, such as the crisis of 1991, were driven by macroeconomic challenges. A successful series of reforms between 1991 and 2004 set the Indian economy on a basis of sound fundamentals, paving the way for rapid growth up to this point. But not all of the necessary reforms were put in place, and as a result, India's political and economic institutions have been unable to keep pace with the country's rapid growth. Inefficiencies and policy distortions have grown more severe, and a recent series of economic shocks and policy missteps have threatened to highlight the cracks in India's economic foundations and throw the country off its growth trajectory entirely – made abundantly clear by the difficulties faced by the export and manufacturing sectors. To return to a path of rapid, inclusive, and sustainable growth, simple economic stimulus is insufficient. India must return to its unfinished reform agenda, introducing policies concerning land acquisition, labor law reform, mobilization of capital and ease of doing business which will bring Indian economic governance in line with the realities of a rapidly growing power operating within a highly globalized world. If India does not summon the political will to implement these reforms, then it will very likely witness marginalization in global supply chains, continued unemployment and economic stagnation, and ultimately the sacrifice of its demographic dividend.
Keywords: 330